MyHcI-UX: taking HCI in Malaysia to greater heights - Ghazali, Masitah; Mahmud, Murni; Sari, Eunice (Association for Computing Machinery, 2019)
The Kuala Lumpur ACM SIGCHI chapter, myHCI-UX, is now two years old. HCI was first starting to find its place in Malaysia circa 2005–2007, when many Malaysian researchers were returning home after completing their postgraduate degrees in HCI. After many meet-ups of HCI academics and practitioners, support from ACM SIGCHI, and with the urge to make a difference and to contribute back to society, the chapter was officially formed on July 27, 2017.